Measurements of branching fractions and time-dependent CP-violating asymmetries in B --> eta'K decays. - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Karyotakis, Y; Lees, J; Poireau, V; Tisserand, V; Zghiche, A; Grauges-Pous, E; Palano, A; Pompili, A; et al. (2005)
We present measurements of the B --> eta(')K branching fractions; for B(+) --> eta(')K(+) we measure also the time-integrated charge asymmetry Alpha(ch), and for B(0) --> eta(')K(0)(S) the time-dependent CP-violation parameters S and C. The data sample corresponds to 232 x 10(6) BB pairs produced by e(+)e(-) annihilation at the Upsilon (4S). The results are Beta(B --> eta(')K(+)) = (68.9 +/- 2.0 +/- 3.2) x 10(-6), Beta(B(0) --> eta(')K(0)) = (67.4 +/- 3.2) x 10(-6), Alpha(ch) = 0.033 +/- 0.028 +/- 0.005, S = 0.30 +/- 0.140 +/- 0.02, and C = -0.21 +/- 0.10 +/- 0.02, where the first error quoted is statistical and the second is systematic.